Pengaruh Kebiasaan Konsumsi Teh dan Fast Food terhadap Risiko Anemia pada Remaja Putri di SMA Trensains Tebuireng Jombang - Ummu Zahroh; Yoanita Indra Kumala Dewi (Ficco Scientific Corner, 2024)
Background: Anemia is decrease in hemoglobin levels as well as erythrocyte and hematocrit counts below 11 g/dL. Tea drinking habits and fast food consumption in adolescent girls can inhibit iron absorption and cause iron loss. This study aims to find out the relationship between tea consumption habits and fast food consumption on the anemia status of adolescent girls at Trensains Tebuireng High School, Jombang. Methods: This study is quantitative research using a cross sectional design. The sample of this study is 62 adolescent girls in grades X and XI with inclusion criteria of not taking iron supplements for the past 2 weeks, not having menstruation, and not suffering from infectious diseases such as malaria, tuberculosis, and others. The data was analyzed using the Chi- Square test. Results: Based on the results of the Chi-Square test, a p-value of 0.009 was obtained in the relationship between tea consumption habits and anemia status and a p-value of 0.000 in the relationship between fast food consumption habits and anemia status. Conclusions: There is relationship between tea consumption habits and fast food consumption on anemia status in adolescent girls at Trensains Tebuireng Jombang High School.